Prevalence and Associated Factors of Common Mental Disorders Among Pregnant Mothers in Rural Eastern Ethiopia - Tamiru, Dawit; Misgana, Tadesse; Tariku, Mandaras; Tesfaye, Dejene; Alemu, Daniel; Weldesenbet, Adisu Birhanu; Gebremichael, Berhe; Dheresa, Merga (Frontiers in Psychiatry, 2022)
Abstract Background: Antenatal common mental disorder is a significant public health issue, especially in low- and middle-income countries with an extensive treatment gap. Common mental disorder has multifaceted implications on maternal and fetal health outcomes during pregnancy with long-running economic and social sequels. This study aimed to determine the prevalence of common mental disorder and associated factors among pregnant mothers in eastern Ethiopia, Kersa and Haramaya Health and Demographic surveillance sites. Methods: A community-based cross-sectional study was conducted in Kersa and Haramaya health and demographic surveillance sites from January 30 to April 30, 2021. World Health Organization Self-Reporting Questionnaire (SRQ-20) was used to measure common mental disorder among 1,015 randomly selected pregnant women. Data were collected face-to-face using open data kit software. After data files were downloaded from the server and saved as an excel file, data set were exported to STATA version 14.0 for cleaning, coding, and analysis. Logistic regression was fitted to identify factors associated with common mental disorder. P-values less than 0.05 were considered to declare the presence of statistical significance. Results: The overall prevalence of common mental disorder (SRQ>6) among pregnant women was 37.5% (95% CI: 34.5, 40.5). Current substance use(AOR=1.99, 95% CI 1.37, 2.88), intimate partner violence(AOR=2.67, 95% CI 2.02, 3.53), null parity(AOR= 3.10, 95% CI 1.65, 5.84), gestational age (first trimester (AOR= 2.22, 95% CI 1.01, 4.93)and third trimester (AOR= 1.74, 95% CI 1.31, 2.31)), history of abortion(AOR= 2.03, 95% CI 1.27, 3.24), and absence of antenatal care follow-up(AOR= 1.43, 95% CI 1.08, 1.89)were significantly associated with common mental disorder during pregnancy. Conclusions: Common mental disorder is prevalent among pregnant women in the study area with significant correlates. Administration of regular screening programs for maternal mental health conditions in rural, low-income communities, integrating into primary health care settings is imperative to reduce the risk.